The impact of surface Cu2+ of ZnO/(Cu1−xZnx)O heterostructured nanowires on the adsorption and chemical transformation of carbonyl compounds. Issue 14 (8th March 2021) - Liu, Jiangyang; Nagashima, Kazuki; Nagamatsu, Yuki; Hosomi, Takuro; Saito, Hikaru; Wang, Chen; Mizukami, Wataru; Zhang, Guozhu; Samransuksamer, Benjarong; Takahashi, Tsunaki; Kanai, Masaki; Yasui, Takao; et al.
Abstract : Unexpected features of surface Cu 2+ on ZnO/(Cu1− x Zn x )O nanowires for molecular transformation and electrical sensing of carbonyl compounds were found. Abstract : The surface cation composition of nanoscale metal oxides critically determines the properties of various functional chemical processes including inhomogeneous catalysts and molecular sensors. Here we employ a gradual modulation of cation composition on a ZnO/(Cu1− x Zn x )O heterostructured nanowire surface to study the effect of surface cation composition (Cu/Zn) on the adsorption and chemical transformation behaviors of volatile carbonyl compounds (nonanal: biomarker). Controlling cation diffusion at the ZnO(core)/CuO(shell) nanowire interface allows us to continuously manipulate the surface Cu/Zn ratio of ZnO/(Cu1− x Zn x )O heterostructured nanowires, while keeping the nanowire morphology. We found that surface exposed copper significantly suppresses the adsorption of nonanal, which is not consistent with our initial expectation since the Lewis acidity of Cu 2+ is strong enough and comparable to that of Zn 2+ . In addition, an increase of the Cu/Zn ratio on the nanowire surface suppresses the aldol condensation reaction of nonanal. Surface spectroscopic analysis and theoretical simulations reveal that the nonanal molecules adsorbed at surface Cu 2+ sites are not activated, and a coordination-saturated in-plane square geometry of surface Cu 2+ is responsible for the observed weak molecular adsorption behaviors. This inactive surface Cu 2+ well explains the mechanism of suppressed surface aldol condensation reactions by preventing the neighboring of activated nonanal molecules. We apply this tailored cation composition surface for electrical molecular sensing of nonanal and successfully demonstrate the improvements of durability and recovery time as a consequence of controlled surface molecular behaviors.